Assessment of the efficacy and safety of anti-sclerostin antibody therapy for osteoporosis in postmenopausal women: a systematic review and meta-analysis of randomized controlled trials - Chen, Lianzhi; Wang, Qingwen; Gu, Mingxi (Frontiers in Endocrinology, 2026)
ObjectiveAnti-sclerostin antibodies are novel biologics for the treatment of postmenopausal osteoporosis, while their efficacy and safety are yet to be fully understood. The aim of this systematic review and meta-analysis is to evaluate the efficacy and safety of anti-sclerostin antibodies compared to placebo, alendronate, teriparatide and denosumab in the treatment of osteoporosis.MethodsThis systematic review and meta-analysis included a total of 10 randomized controlled trials (RCTs),involving 12,384 participants with postmenopausal osteoporosis, comparing anti-sclerostin antibodies with alendronate, teriparatide, denosumab, or placebo in postmenopausal women with osteoporosis. The quality of randomized controlled trials was evaluated by using the Cochrane Collaboration’s Randomized Controlled Trial Risk of Bias Assessment Tool, and meta-analysis was performed by using the RevMan software. The primary outcome was the percentage change in bone mineral density(BMD)at 6 and 12 months compared to baseline. Secondary outcomes included the incidence of adverse events and cardiovascular complications.ResultsCompared with placebo, alendronate, and teriparatide, anti-sclerostin antibodies significantly increased BMD at the lumbar spine, total hip, and femoral neck at 6 and 12 months. Compared with denosumab, anti-sclerostin antibodies significantly increased lumbar spine bone mineral density at 6 months (MD = 3.68, 95% CI: 0.34-7.01, P = 0.03) and 12 months (MD = 5.20, 95% CI: 3.19–7.21, P < 0.00001). No significant differences in BMD were found at the total hip and femoral neck versus denosumab. Regarding safety, anti-sclerostin antibodies had a lower incidence of adverse events than alendronate (RR = 0.96, 95% CI: 0.93–0.99, P = 0.02) but a higher incidence than teriparatide (RR = 1.13, 95% CI: 1.01–1.25, P = 0.03). There was no significant difference in adverse events compared to placebo (RR = 0.98, 95% CI: 0.96–1, P = 0.1) or denosumab (RR = 2.64, 95% CI: 0.74–9.36, P = 0.13). Importantly, anti-sclerostin antibodies did not significantly increase the risk of cardiovascular complications compared to other treatments (RR = 1.23, 95% CI: 0.92–1.64, P = 0.17).ConclusionAnti-sclerostin antibodies are effective at increasing BMD, with a pronounced effect on the lumbar spine, and demonstrate a controllable overall risk profile. The study results demonstrate that anti-sclerostin antibodies can be used to treat postmenopausal osteoporosis.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/recorddashboard, identifier CRD420251103597.